2006
DOI: 10.1038/sj.emboj.7601014
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale identification of genes implicated in kidney glomerulus development and function

Abstract: To advance our understanding of development, function and diseases in the kidney glomerulus, we have established and large-scale sequenced cDNA libraries from mouse glomeruli at different stages of development, resulting in a catalogue of 6053 different genes. The glomerular cDNA clones were arrayed and hybridized against a series of labeled targets from isolated glomeruli, non-glomerular kidney tissue, FACS-sorted podocytes and brain capillaries, which identified over 300 glomerular cell-enriched transcripts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
215
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(227 citation statements)
references
References 81 publications
11
215
1
Order By: Relevance
“…Previous studies showed that knockout of several transcription factors expressed in podocytes (Pod1, Foxc2, Limx1b, and Krm1/MafB) resulted in a decreased number of capillary loops and abnormal mesangium similar to what we observed in our study. [33][34][35][36] Therefore, S1P1 may be involved in the interactions among podocytes, ECs, and mesangium to regulate the development of the glomerular capillary loops. Whether S1P1 operates through the transcription factors mentioned earlier requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that knockout of several transcription factors expressed in podocytes (Pod1, Foxc2, Limx1b, and Krm1/MafB) resulted in a decreased number of capillary loops and abnormal mesangium similar to what we observed in our study. [33][34][35][36] Therefore, S1P1 may be involved in the interactions among podocytes, ECs, and mesangium to regulate the development of the glomerular capillary loops. Whether S1P1 operates through the transcription factors mentioned earlier requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…GLCCI1 gene is highly expressed in lymph nodes, leukocytes, breast, testis, adrenal, lungs, kidneys and others [21]. Because of high glomerul expression [22] GLCCI1 rs37973 was also analysed on patients with nephrotic syndrome receiving oral steroids, however no pharmacogenetic association was found [23]. On lymphoblastoid B cells variants in GLCCI1 were shown to be associated with decreased expression of GLCCI1, both at baseline and in response to dexamethasone treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy can significantly increase the resolution of the screen. One approach has profiled small subsets of cells generated through dissection (Mitchell et al, 2006), cell sorting (Takemoto et al, 2006), or laser-capture microdissection (Potter et al, 2007). The resulting profile provides more specific information about the cell "state" of the profiled population.…”
Section: Profiling Cell Statementioning
confidence: 99%